Clinical profile and outcome of acute organophosphate poisoning in children of Upper Egypt: a cross-sectional study - Khaled A. Abdel Baseer; Eman Fathala Gad; Yaser F. Abdel Raheem (BMC, 2021)
Abstract Background Organophosphates are one of the most common agents of poisoning in developing countries including Egypt. Due to lack of data about characteristics of organophosphates poisoning in our localities, we aimed to evaluate its clinical pattern and factors affecting outcome. Methods It was a cross-sectional study conducted in South valley University hospital between January 2019 and December 2019. It included all children ≤16 years of age presented with organophosphates poisoning. Diagnosis was performed from the history taken from the patient's relatives and presenting symptoms. Demographic data, mode and route of poisoning, time from exposure to presentation, clinical symptomatology, grading and routine investigations were evaluated in addition to treatment taken and outcome. Results During the study period, 108 children; mean age was 7.95 ± 4.11 years (range 1. 5-16 years) presented with organophosphorous poisoning. Sixty five (60%) cases were females and 43 (40%) were males. Unintentional acts (87%) were detected more than suicidal (13%) and inhalation route (63.8%) more than ingestion (36. 2%). Miosis was the most frequent clinical sign (100%) followed by respiratory distress (77.7%). Regarding time of presentation to emergency department, 43 (40%) cases were presented within 6 h while others presented more than 6 h post-exposure. Mechanical ventilation (MV) was needed for 14 (13%) cases and 6 (5.5%) cases died due to respiratory failure. Duration of hospital stay, mean time interval from toxic exposure to hospital presentation, leucocytosis, need for MV and cumulative dose of pralidoxime were significantly higher in non survivors than survivors while Pao2 (partial arterial oxygen) and GCS (Glasgow coma scale) were significantly lower. Conclusion This study concluded that time consumed till presentation to hospital, low GCS, need for MV, leucocytosis, decreased PaO2 and increased cumulative dose of pralidoxime were independent risk factors of mortality.